ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PENGEMBANGAN SUMBER DAYA MANUSIA PADA PEGAWAI DINAS KESEHATAN KABUPATEN BUTON UTARA - Budi Ansar; Adius Kusnan; Devi Savitri Effendi (NHM PRESS, 2022)
The development of directed and planned human resources accompanied by good management will save other resources or at least the processing and use of organizational resources can be efficient and effective. This study aims to analyze the factors that influence the development of human resources in the health service employees of North Buton Regency. Method. This cross sectional study was conducted in September-October 2022 involving 45 respondents at the Health Office of North Buton Regency. Data were processed and analyzed using bivariate test using chi square, multivariate test using logistic regression. Variables that have a P-value <0.05 are considered significant. The most dominant respondent's HR development is the effective category as many as 26 respondents (57.8%), and the least is the ineffective category as many as 19 respondents (42.2%). The results of the chi square test show that the development of health human resources in North Buton Regency is related to the mission and goals of the organization (P-value = 0.000), strategies for achieving organizational goals (P-value = 0.000), government policies (P-value = 0.000), social and culture (P-value = 0.000), development of science and technology (P-value 0.000). The conclusion of the study is that the development of Health HR in North Buton Regency is most related to the strategy for achieving organizational goals with an R Square value of 87.5%.